Rupture Geometry and Slip Distribution of the Mw 7.2 Nippes Earthquake, Haiti, From Space Geodetic Data. (22nd April 2023) - Raimbault, B.; Jolivet, R.; Calais, E.; Symithe, S.; Fukushima, Y.; Dubernet, P.
Abstract: On 14 August 2021 the Mw 7.2 Nippes earthquake struck southern Haiti, rupturing a segment of the Enriquillo‐Plantain Garden Fault system (EPGF), a 300 km‐long strike‐slip fault system that accommodates half of the highly oblique convergence displacement between the Caribbean and the North American plates. We use coseismic surface displacements from Interferometric Synthetic Aperture Radar and Global Navigation Satellite System (GNSS) to estimate the geometry of the rupture through a systematic parametric exploration, determine its mechanism, and relate them to the regional tectonics derived from interseismic GNSS measurements. We show that the earthquake ruptured a north dipping fault (66 ± 4° dip) with a geodetically determined moment release that is 40% reverse and 60% strike‐slip. We cannot conclude whether this north‐dipping structure is the EPGF itself or a distinct fault running parallel to the EPGF. The rupture then evolved to the west on a vertical (86 ± 2° dip) fault parallel to the EPGF, the Ravine du Sud fault, with left‐lateral strike‐slip motion. The coseismic slip distribution of the 2010 Léogane and 2021 Nippes earthquakes, consistent with the transpressional interseismic strain rate field, show a segmentation of the Caribbean–North American plate boundary in southern Haiti and imply a revision in our understanding of the mode of earthquake rupture within the EPGF system. Plain Language Summary: On 14 August 2021, a magnitude Mw 7.2 earthquake struck the Southern Peninsula of Haiti, a Caribbean country highly vulnerable to natural hazards. Haiti's Peninsula is the locus of the Enriquillo‐Plantain Garden Fault (EPGF), known to accumulate elastic strain susceptible to be released in earthquakes to come. We use satellite radar images and Global Navigation Satellite System (GNSS) data acquired in the epicentral areas of the earthquake to investigate the geometry of the fault involved in the earthquake, the fault motion, and how they match the long‐term, decadal‐scale, regional deformation pattern derived from GNSS data. We show that the earthquake first ruptured a north‐dipping fault (66 ± 4°) and continued to the west on a vertical strike‐slip (86 ± 2°) fault corresponding to the mapped Ravine du Sud fault. We cannot conclude whether this north‐dipping structure is the EPGF itself or a distinct fault running parallel to the EPGF. We show that the fault motion during the earthquake is consistent with the long‐term deformation pattern, with strong similarities with the devastating 2010 event which did not rupture the EPGF. These events show an unexpected segmentation of the fault system that is not yet accounted for in the regional earthquake hazard maps. Key Points: We present geodetic observations (Global Navigation Satellite System and Interferometric Synthetic Aperture Radar) constraining the slip distribution of the Haiti Nippes earthquake, 2021, on two faults Mechanisms of the 2010 and 2021 earthquakes confirm the interseismic accumulation of transpressional strain within the Southern Peninsula We highlight the role of segmentation on dynamics of stress release along the Enriquillo‐Plantain Garden Fault system with significant implications on seismic hazard